The significance of tasks in second language learning: The case of Africa University in Zimbabwe - Mvundura, Emmaculate; Svongoro, Paul (Goodwood Publishing, 2021)
Purpose: This study utilised the case study approach for an in-depth understanding of the practices of teaching English as a Second Language (ESL) at Africa University (AU), Zimbabwe. The study aimed to provide a description of unique and typical ESL experiences in a particular African context. Research Methodology: The study investigated 60 participants who were prospective undergraduate students enrolled in the ESL programme and were separated into two groups. Each group consisted of 30 participants who received task-based instruction hinged on reading, writing, listening, and speaking. Result: An analysis of the learners' performance revealed that tasks facilitate the learning of ESL by exposing learners to different problem-solving scenarios that required higher-order cognitive skills. Limitations: This study was based on the ESL classroom at AU, which enrols students from African countries. A similar study could be conducted with students from more diverse backgrounds to establish if the results of this study could be corroborated or refuted. Similar studies could also be conducted in other second language contexts where English is not the target language. Contribution: The results of this study are important for the discipline of ESL as they support existing knowledge that tasks allow learners to communicate using the correct grammatical structures in a given relevant context.